P-majorizing quadratic stochastic operators - Saburov, Mansoor; Yusof, Nur Atikah (Ukrainian National Academy of Sciences, 2017)
In this paper, we introduce a new class of the so-called p-majorizing quadratic stochastic operators which is the generalization of the class of quadratic doubly stochastic operators. We provide a criterion for the regularity of p-majorizing quadratic stochastic operators acting on 2D simplex. Some relevant examples are also provided.